Manajemen Diri Dalam Meningkatkan Kecapakan Literasi Digital dan Kritikal Bagi Para Pebelajar Masa Pandemi Covid-19 - Imam Azhar (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2020)
Whatever literacy is, it [has] something to do with reading. And reading is always reading something. Furthermore, if one has not understood [made meaning from] what one has read then one has not read it. So reading is always reading something with understanding. [T]his something that one reads with understanding is always a text of a certain type which is read in a certain way. The text might be a comic book, a novel, a poem, a legal brief, a technical manual, a textbook in physics, a newspaper article, an essay in the social sciences or philosophy, a “self-help” book, a recipe, and so forth through many different types of text. Each of these different types of text requires somewhat different background knowledge and somewhat different skills. (Gee, Hull, & Lankshear, 1996). In this essay, the writer talked about several kinds of literacies; they are critical litercay, digital literacy, contemporerary literacy, and the benefit of them to the learning proces. Here, Critical literacy is defined as the ability to take apart various texts in media or writing to find any possible discrimination that the author might have embedded in his or her presentation of the world since authors have social and political influence. Critical literacy happens when readers examine the social, political and cultural purposes and values that the texts reflect. Critical readers may ask who is behind the text, and why the argument is being made. They may ask whose voices are missing from the text. They may “talk back” to the text, and construct different readings of it. Then they are becoming “text critics. While, Digital literacy is as the ability to understand and use information in multiple formats from a wide range of sources when it is presented via computers.The awareness, attitude and ability of individuals to appropriately use digital tools and facilities to identify, access, manage, integrate, evaluate, analyse and synthesise digital resources, construct new knowledge, create media expressions, and communicate with others, in the context of specific life situations, in order to enable constructive social action; and to reflect upon this process. Contemporary Literacy its self meant by several leteracies as technology leteracy, information leteracy, communication leteracy, internet literacy, dan Internet information literacy. It concluded that all students should be aware and concious about literacy especially in the pandemic ‘COVID-19’